Political Dynamics and Their Implications For the Constitutional Court - M. Iqbal Pratama (Journal of Law, Politic and Humanities, 2026)
The Constitutional Court of the Republic of Indonesia (MKRI) is a legal institution tasked with maintaining the applicability of the constitution and ensuring that the principles of the rule of law run well in the Indonesian government system. Since its establishment in 2003, the MKRI has become an important venue where legal and political issues often collide, especially in handling cases with major political impact, such as disputes over election results, challenges to laws and regulations, and the dissolution of political parties. The intensification of political dynamics poses a major challenge to the independence and credibility of the MKRI, especially amid political polarization and authorities' interference with legal institutions. This article analyzes in depth how changes in national politics affect the Constitutional Court's duties and functions. By using a legal approach grounded in norms and supported by a conceptual analysis of several MKRI decisions with political nuances, this study seeks to explain various forms of political influence on the MKRI's decision-making process. In addition, this article discusses strategic steps to strengthen the MKRI's independence amid intensifying political pressure. The results of the study show that political dynamics significantly affect the MKRI's performance and reputation. The MKRI's involvement in resolving political conflicts often puts him in a difficult position, namely between maintaining neutrality and meeting people's expectations of real justice. Therefore, continuous improvement is needed in the mechanism for recruiting judges, increased transparency in decisions, and strengthened public supervision of the constitutional judiciary's honesty.